Screening for congenital hypothyroidism in Malang, East Java in 2020 - Irfan Agus Salim; Berlian Ristina Putri; Tiara Afia Rosmalawati; Haryudi Aji Cahyono; Fadhilah Muttaqin (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: Congenital hypothyroidism is defined as a state of thyroid hormone deficiency present at birth. Congenital hypothyroidism must be diagnosed immediately because delay in therapy may cause irreversible neurological deficits, such as mental retardation in children. However, this condition can be prevented by screening in newborns so that congenital hypothyroidism can be diagnosed and treated early, and can result in better neurological development. This study aims to determine the congenital hypothyroidism ratio in Malang from March to November 2020. Methods: The descriptive analysis method was used in this research. The subjects were neonates aged 0 – 28 days with a gestational age of 36 weeks and were involving the Health Office in both the Regency and the City of Malang. The data about identity, gender, age at screening, and gestational age were collected. A laboratory screening test was performed by taking a blood sample from the heel or vein for a TSH test. If the result was positive with a TSH value > 20 U/mL, the subject would be recalled for having a confirmation test and referred to a pediatric endocrinologist. Results: There were 2024 (88.34%) subjects were successfully screened from a total of 2291 subjects. The recall rate for congenital hypothyroidism was 1:2024 (0.04%). Conclusion: The ratio of congenital hypothyroidism cases in Malang from March to November 2020 was higher than the global ratio, which was 1:3000. The high rate of congenital hypothyroidism in Malang indicated the need for congenital hypothyroidism screening in newborns.